STUDI DESKRIPTIF DAMPAK POLA KOMUNIKASI ORANGTUA TERHADAP PERKEMBANGAN BAHASA LISAN PADA ANAK USIA 4-5 TAHUN DI DUSUN DAMPEK DESA SATAR PADUT KECAMATAN LAMBA LEDA : STUDI DESKRIPTIF DAMPAK POLA KOMUNIKASI ORANGTUA TERHADAP PERKEMBANGAN BAHASA LISAN PADA ANAK USIA 4-5 TAHUN DI DUSUN DAMPEK DESA SATAR PADUT KECAMATAN LAMBA LEDA - Maria Fatima Mardina Angkur; Fransiskus De Gomes; Merici Agustina (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
This research is motivated by the fact that there are still children aged 4-5 years who experience obstacles to the development of spoken language. This study aims to determine the types of patterns and the impact of parental communication patterns on the development of spoken language for children aged 4-5 years in Dampek Hamlet, Satar Padut Village, Lamba Leda District. The approach in this study used a qualitative descriptive approach with the research subjects of parents and children aged 4-5 years. Data was collected using open interviews, observation and documentation. The data analysis technique uses the Miles and Huberman model. Testing the validity of the data using triangulation techniques. The results showed that parental communication patterns that were unidirectional or authoritarian had a negative impact on the oral language development of children aged 4-5 years with a total of 6 children experiencing barriers and at the stage of starting to develop while 4 other children used two -way (democratic) communication patterns, reaching the stage of development in accordance with expectations is proven to have a positive impact on children. The negative impact of unidirectional (authoritarian) communication patterns in the form of children tend to be insecure and silent when spoken to and communicated by teachers and their friends. While the two-way (democratic) communication pattern has a positive impact and supports the development of children's spoken language, which is reflected in the attitude of being able to tell experiences confidently without feeling afraid.